APLIKASI KATALIS CaO DALAM PEMBUATAN BIODIESEL DARI MINYAK GORENG BEKAS - Jolantje Latupeirissa; I Wayan Sutapa; Harniati P Rego (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2012)
The research of biodiesel from waste cooking oil using CaO as catalyst with two step esterification and transesterification has been done. On esterificatioan step, methanol and waste cooking oil mol ratio is 1:9 with H2SO4 1 M as catalyst. On transesterification process using CaO catalyst is 1:12 on 60-65 oC for 5 hours. Theoritically, biodiesel which resulted is 48,342 % while by experimentally is 30,93 %. The main component which resulted are methyl oleate (42,77%) and biodiesel based on ASTM data results specific density (0,8746), kinematic viscosity (4,706), flash point (170,5), pour point (12) and carbon conradson remaining (0,0193)